2015
DOI: 10.1001/jama.2015.12076
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Lavage vs Primary Resection for Acute Perforated Diverticulitis

Abstract: clinicaltrials.gov Identifier: NCT01047462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(190 citation statements)
references
References 26 publications
4
177
0
9
Order By: Relevance
“…In the laparoscopic era, colorectal surgeons may agree to attempt laparoscopic management of colorectal perforation following colonoscopy, diverticulitis, and anastomotic leakage [9][10][11][12]. The SCANDIV trial showed that laparoscopic lavage for perforated diverticulitis is no better than conventional operations; laparoscopic lavage did not reduce morbidity and had worse outcomes, such as high reoperation rate and missing carcinoma [9].…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…In the laparoscopic era, colorectal surgeons may agree to attempt laparoscopic management of colorectal perforation following colonoscopy, diverticulitis, and anastomotic leakage [9][10][11][12]. The SCANDIV trial showed that laparoscopic lavage for perforated diverticulitis is no better than conventional operations; laparoscopic lavage did not reduce morbidity and had worse outcomes, such as high reoperation rate and missing carcinoma [9].…”
Section: Discussion:-mentioning
confidence: 99%
“…The SCANDIV trial showed that laparoscopic lavage for perforated diverticulitis is no better than conventional operations; laparoscopic lavage did not reduce morbidity and had worse outcomes, such as high reoperation rate and missing carcinoma [9]. Another randomized controlled trial, however, reported that laparoscopic lavage may be an appropriate treatment option, though the condition in question was different [10]. Lee et al reported that laparoscopic reintervention for anastomotic leakage was associated with shorter hospitalization and fewer complications [12].…”
Section: Discussion:-mentioning
confidence: 99%
“…[29,30] Laparoscopic lavage in the short term was associated with increased morbidity and mortality with higher re-intervention rates when compared to sigmoid resection. Long term results from these studies will be required to determine if any long term advantages to minimally invasive treatments such as stoma avoidance and long term need for surgical intervention are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the technique has not gained a wide acceptance and, up to date, three randomized controlled trials (RCTs) comparing LL to sigmoidectomy have been published [47-49]. Interestingly, their conclusions did not agree and the strong debate raised from these conflicting results led 7 meta-analyses to be published over the last 2 years [50-56].…”
Section: Operative Treatmentmentioning
confidence: 99%